Faktor yang Berhubungan dengan Tingkat Kepuasan Masyarakat Desa Seumet dalam Memanfaatkan Puskesmas Montasik Aceh Besar Tahun 2024 - Anis Miska. MZ; Farrah Fahdhienie; Verra Nazhira (Jurnal Ilmu Kesehatan dan Gizi, 2026)
The utilization of community health centers remains challenging, although primary health care facilities continue to develop. This study was conducted to examine the determinants associated with the level of satisfaction among residents of Seumet Village regarding the healthcare services delivered by Montasik Community Health Center in Aceh Besar. This study employed an analytical descriptive design using a cross-sectional approach. The study population comprised 495 residents of Seumet Village, while 84 respondents were selected using the Slovin formula. Primary data were gathered through interviews guided by structured questionnaires, while secondary data were derived from health agencies and pertinent literature sources. The independent variables encompassed reliability, responsiveness, assurance, empathy, and tangible aspects, whereas community satisfaction was positioned as the dependent variable. Data analysis was undertaken through univariate and bivariate procedures, with the Chi-square test applied at a 95% confidence interval. The findings revealed that each dimension of service quality had a statistically meaningful relationship with the level of community satisfaction. Reliability, responsiveness, assurance, empathy, and tangible evidence contributed to service experiences perceived as satisfactory. The health center is advised to improve service accuracy, staff responsiveness, procedural certainty, friendliness, facility comfort, administrative flow, communication, and supporting infrastructure for residents on an ongoing basis.